Formulation, in silico, in vitro characterization, cytotoxicity and cellular uptake of cyclodextrin complexes and ion pairing/salt formation with functional excipients (azelaic acid, tartaric acid, and arginine) with raloxifene - Hamdy Abdelkader; Adel Al-Fatease; Ali H. Alamri; Mai E. Shoman; Hend Mohamed Abdel-Bar; Zeinab Fathalla (International Journal of Pharmaceutics: X)
With advancements in drug repurposing, the search for effective and less harmful anticancer agents remains a critical endeavor. Raloxifene, although not a typical anticancer drug, holds promise in this context. However, its poor solubility poses a significant challenge to its therapeutic potential and formulation efficiency. Functional excipients such as cyclodextrins (e.g., β-cyclodextrin, hydroxy propyl β-cyclodextrin, and Captisol) and pH-modifying excipients (e.g., tartaric acid, azelaic acid, and arginine) were investigated to enhance solubility, dissolution, cytotoxicity and cellular uptakes employing Caco-2 cell lines through binary solid dispersions. In silico studies suggested the potential for salt formation with raloxifene-azelaic acid and raloxifene-tartaric acid, as well as inclusion complexes with cyclodextrins. Experimental results showed that pH-modifying excipients, particularly tartaric and azelaic acids, significantly improved solubility (up to an 800-fold increase), outperforming cyclodextrins (8-fold increase) compared to the untreated drug. Cytotoxicity studies on the human breast cancer (Michigan cancer foundation, MCF-7) cells revealed that raloxifene-tartaric acid significantly enhanced cell killing, achieving efficacy comparable to the standard anticancer drug Taxol. Additionally, both fluorescence-labeled raloxifene: hydroxy propyl β-cyclodextrin coprecipitated mixtures (Coppt) and raloxifene: tartaric acid Coppt exhibited concentration- and time-dependent cellular uptake, with mean fluorescence intensity increasing significantly at 24 h, indicating rapid internalization and sustained intracellular retention, especially at higher concentrations. More interestingly, the superior cellular uptake was in favor of the latter, indicating the pH-modifying excipient tartaric acid, and these findings correlated well with solubility and dissolution studies.